Rejuvenating Technical Vocational Education and Training Programmes in Polytechnics Amid the Covid-19 Pandemic for Poverty Reduction and Economic Recovery in Nigeria - Owo, Offia Tugwell; Ajie, Prince Maduabuchukwu (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
The study determined the challenges of technical vocational education and training programmes in polytechnics in Nigeria. The study which adopted descriptive survey design used purposive sampling technique to obtain a sample of 518 subjects (consisting of 98 electrical/electronic engineering lecturers and 420 final year students. One research question and one hypothesis guided the study. A 10-item questionnaire titled â€œConstraints to Effective TVET Programmes in Polytechnics Questionnaire (CETPPQ)â€, was used for the study. Mean and standard deviation were descriptive statistical tools adopted to analyze the research questions while t-test was the inferential statistics used to test the null hypotheses at 0.05 level of significance. The findings revealed among others that lack of teaching staff, inadequate funding, inadequate training facilities among others modern equipment and tools, defective curricula, poor professional development of staff, poor institution-industry synergy, among others constitute constraints to quality polytechnic education in Nigeria. Consequently, it was recommended among others that government should provide requisite human and material resources needed for quality TVET programmes in Nigerian polytechnics for skill training of technology students.